Improvement in the performance with less stiff air layer formation around the rubber tube-pasted grinding wheel. (August 2019) - Guha, Spandan; Das, Partha Protim; Chakraborty, Shankar
In the grinding operation, a stiff layer of air gets formed around the periphery of the grinding wheel that causes deterioration of its performance. In the present work, in order to restrict the generation of stiff air layer around the periphery of the grinding wheel, a rubber tube is pasted on its surface to improve the grinding performance. An experimental investigation is carried out with low alloy steel as the work material. Taguchi's L 9 orthogonal array is considered for the design of experiments while taking cutting speed, depth of cut, and type of the cutting fluid as the input grinding parameters. A comparative analysis using rubber tube-pasted grinding wheel and normal grinding wheel reveals that the developed wheel significantly improves the grinding performance with respect to surface roughness, amplitude of vibration and grinding ratio, as compared to the normal wheel. Moreover, grey relational analysis aided with fuzzy logic is applied in the experimental results to derive the optimal combination of process parameters for further enhancement of the grinding performance. Finally, analysis of variance results identify cutting speed as the most significant parameter while grinding with normal wheel, whereas depth of cut appears to be the most important parameter while machining with rubber tube-pasted grinding wheel.